2008
DOI: 10.1038/leu.2008.95
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase-1 is a downstream regulator of imatinib-induced apoptosis in chronic myeloid leukemia cells

Abstract: We examined the involvement of sphingosine kinase-1 (SphK1), which governs the ceramide/sphingosine-1-phosphate balance, in susceptibility to imatinib of either sensitive or resistant chronic myeloid leukemia cells. Imatinib-sensitive LAMA84-s displayed marked SphK1 inhibition coupled with increased content of ceramide and decreased pro-survival sphingosine-1-phosphate. Conversely, no changes in the sphingolipid metabolism were observed in LAMA84-r treated with imatinib. Overcoming imatinib resistance in LAMA8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 37 publications
7
69
1
2
Order By: Relevance
“…It was also shown that intracellular concentrations of ceramides are increased in response to stress conditions. But in cancerous tissues and cells and in more agressive resistant cell expressions, levels of GCS and SK-1 increases significantly [26][27][28].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was also shown that intracellular concentrations of ceramides are increased in response to stress conditions. But in cancerous tissues and cells and in more agressive resistant cell expressions, levels of GCS and SK-1 increases significantly [26][27][28].…”
Section: Introductionmentioning
confidence: 97%
“…Ceramides act as strong antitumoral molecules supressing cell growth and proliferation and inducing apoptosis and differentiation [26]. On the other hand, GlcCer and S1P molecules converted from ceramide by glucosylceramide synthase (GCS) and sphingosine kinase-1 (SK-1) enzymes act as strong antiapoptotic molecules inducing cell growth and proliferation and inhibiting apoptosis and differentiation [27,28]. Thus, the balance between ceramide/GlcCer or ceramide/S1P significantly affects the fate of the cell to die or to survive.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, antibodies targeting S1P have been recently shown to have a significant antineoplastic potential (11), and clinical trials using inhibitors of SphK1 in combination with chemotherapeutic treatments are ongoing for chemotherapy-resistant ovarian cancers and hormonerefractory prostate cancers. Recently, we and other groups have correlated resistance to anticancer therapies of several cancer cell lines with a defect in both ceramide production and/or SphK1 inhibition (9,12,13). In these conditions, the concept that SphK1 inhibition might sensitize resistant cancer cells to these inefficient therapies has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Imatinib was the first tyrosine kinase inhibitor used to specifically recognize the adenosine triphosphate (ATP) binding site of the BCR-ABL protein. However, its continuous administration was associated with the development of resistance, especially in the advanced phase or blast crisis [8]. Different mechanisms were suggested for imatinib resistance [9,10] such as mutations in the ATP binding site of BCR-ABL [11], decreased availability of the drug either by binding to plasma proteins or by overexpression of transporter proteins such as P-glycoprotein on the plasma membrane [12], or overexpression of BCR-ABL.…”
Section: Introductionmentioning
confidence: 99%